A single‐nucleotide polymorphism in lnc‐LAMC2‐1:1 interferes with its interaction with miR‐128 to alter the expression of deleted in colorectal cancer and its effect on the survival rate of subjects with ovarian cancer - Wang, Qian; Li, Xiao‐Ping; Zhou, Xi; Yang, Chun‐Fen; Zhu, Zhu (Journal of cellular biochemistry, 2020)
This study aimed to identify the association between lnc‐LAMC2‐1:1 polymorphism rs2147578 and the recurrence of ovary cancer, as well as to study the underlying mechanism of rs2147578 in ovary cancer. Real‐time polymerase chain reaction, Western blot analysis, immunohistochemistry, 3‐(4,5‐dimethylthiazol‐2‐yl)‐2,5‐diphenyltetrazolium bromide assay, Logrank test, and Kaplan‐Meier analysis were carried out to explore the role of rs2147578 in ovary cancer. No obvious difference was observed concerning all clinical characteristics among 90 patients genotyped as CC (N = 28), CG (N = 38), and GG (N = 24) in their rs2147578 polymorphism. In addition, the subjects carrying the CC genotype had longer recurrence‐free survival time and showed a lower level of malignancy compared with those carrying CG and GG genotypes. Lnc‐LAMC2‐1:1 and miR‐128 were lowly expressed in the CC group, while deleted in colorectal cancer (DCC) was highly expressed in the CC group. Furthermore, DCC was identified as a target gene of miR‐128, and miR‐128 mimics decreased the luciferase activity of cells cotransfected with wild‐type DCC 3′‐untranslated region. Lnc‐LAMC2:1‐1 directly targeted and affected miR‐128 expression, and the G allele in lnc‐LAMC2‐1:1 rs2147578 upregulated miR‐128 expression. Transfection with a miR‐128 precursor evidently downregulated the expression of lnc‐LAMC2‐1:1, miR‐128, and DCC expression, but did not affect the expression of ABCC5 and body mass index. Finally, miR‐128 precursor promoted cell proliferation and inhibited cell apoptosis. Compared with lnc‐LAMC2‐1:1 rs2147578C allele, the G allele increases the risk of ovarian cancer by reducing the binding between lnc‐LAMC2‐1:1 and miR‐128‐3p, which in turn further decreases the expression of DCC and inhibits cell apoptosis. This study aimed to identify the association between lnc‐LAMC2‐1:1 polymorphism rs2147578 and the recurrence of ovary cancer, as well as to explore the mechanisms underlying the role of rs2147578 in ovary cancer. As a result, we found that the lnc‐LAMC2‐1:1 rs2147578G allele may increase the risk of ovarian cancer by reducing the binding between lnc‐LAMC2‐1:1 and miR‐128‐3p, which in turn further decreases the expression of deleted in colorectal cancer and inhibits cell apoptosis.